Sistem Pendukung Keputusan Dalam Penentuan Penerima Beasiswa PT BFI Finance Indonesia Tbk Menggunakan Metode Profile Matching - Raden Ajeng Yosua Ariane Amos Wiseso; Johan Setiawan (ULTIMA InfoSys, 2018)
This research is conducted to know and develop the process of determining scholarship recipients in BFI Finance Indonesia Tbk which until now still done by manual process. Based on interview, it was found that there has been a delay in decisionmaking from the deadline that has been determined. From this study the authors hope to help decision makers to be able to use the system that has been made in order to help the decision-making process. The problem discussed in this research is how the implementation of Profile Matching method is used in determination of scholarship recipients of PT BFI Finance Indonesia Tbk.? Profile Matching method is used to provide recommendations of students who are entitled to get based on the total value that is the result of core factor and secondary factor. The variables used are GPA, Achievement, Psychotest score, and interview value. For core factor attributes: GPA, psychotest score, and interview value, while for secondary factor attribute: achievement. For the total value weighs 80% for core factor and 20% for secondary factor. The result of this research is a rank of candidate based on calculation by web-based decision support system using profile matching method. Index Terms— DSS, Profile Matching, scholarship, BFI, system.